2020
DOI: 10.1186/s12864-020-07128-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional analysis of the TIFY gene family in the response to multiple stresses in Brassica napus L.

Abstract: Background TIFY is a plant-specific protein family with a diversity of functions in plant development and responses to stress and hormones, which contains JASMONATE ZIM-domain (JAZ), TIFY, PPD and ZML subfamilies. Despite extensive studies of TIFY family in many other species, TIFY has not yet been characterized in Brassica napus. Results In this study, we identified 77, 36 and 39 TIFY family genes in the genome of B. napus, B. rapa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 62 publications
(117 reference statements)
6
22
1
Order By: Relevance
“…Therefore, we analyzed the expression of JAZ family genes in turnips under different stress conditions. Our results showed that most BrrJAZs responded significantly to abiotic stress and/or exogenous phytohormone treatments, which is in agreement with the results obtained in other Brassica crops 30 , 40 – 42 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, we analyzed the expression of JAZ family genes in turnips under different stress conditions. Our results showed that most BrrJAZs responded significantly to abiotic stress and/or exogenous phytohormone treatments, which is in agreement with the results obtained in other Brassica crops 30 , 40 – 42 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous research identified 36, 38, 36, and 36 JAZ genes in B. rapa L. 40 , B. juncea var. tumida 41 , B. napus L. 42 , and B. oleracea var. capitata 30 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, GaJAZ5 was found to improve drought resistance, and GsTIFY10a may play positive roles in plant tolerance to bicarbonate stress [40]. Recently, results showed that the BnaJAZ subfamily of genes could be predominantly induced by different abiotic/biotic stresses and hormones in rapeseed [41], which showed similar patterns in B. rapa [42] and B. oleracea [43]. In this study, our findings suppose that all TIFY family genes had a tight evolutionary and phylogenetic relationship (Figures 1 and 4), and may share similar functions in the same subgroup.…”
Section: Discussionmentioning
confidence: 98%
“…The Jas domain could interact with COI1 and transcription factors that were involved in JA signaling pathway [18]. The Arabidopsis, maize, rice, Brassica napus, Camellia sinensis, and soybean genomes encode 13, 26, 15, 52, 13, and 25 JAZs, respectively [13,[19][20][21][22][23]. The JAZ proteins from different plant species could be divided naturally into different numbers of sub-groups based on their evolutionary relationship [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%